Selective Breeding for Genetic Improvement of Nile tilapia (Oreochromis niloticus Linnaeus, 1758) in Uganda: Current Status, Challenges, and Future Perspectives - Abaho, Ivan; Kwikiriza, Gerald; Atukwatse, Faith; Izaara, Andrew A; Ekwangu, Joseph; Baguma, Sylvester D; Kubiriba, Jerome; Kasozi, Nasser (MDPI AG, 2025)
aquaculture continues to significantly contribute to the growth of the aquaculture sector in Uganda. However, its production is beset by erratic and unreliable seed supply. Also, most hatcheries practice inbreeding of broodstock, resulting in inferior seed characterized by low growth rates. As such, a selective breeding program is necessary to readily avail fast-growing seed that respond to farmers' needs. The present review consolidates available information on developing a breeding program in Uganda. The article discusses the significance of genetic improvement, drawing lessons from successful selective breeding programs in other countries. From a literature review, no systematic selective breeding program was traceable in Uganda. Scanty information on the selective breeding efforts of the species was available, with little evidence of selection for improved performance. Overall, the national capacity for aquaculture research and development, including fish breeding and strain improvement, was weak and poorly funded. The review recommends purposive support for developing a systematic strain improvement breeding program, which will be a source of improved broodstock and seed for hatcheries and farmers, respectively. The program would guide the formulation of standard operating procedures for quality seed production towards ensuring sustainable aquaculture growth in Uganda. PubMed